VITAMIN D LEVELS IN MULTIPLE SCLEROSIS - Durmaz, Zeynep Hulya; Ayan, Durmuş; Demir, Aslıhan Dilara; Demir, Hatice Dörtok (Malang Neurology Journal, 2020)
Background: Multiple Sclerosis is a neurologic disease that effect Central Nervous System(CNS). Vitamin D is a liposoluble prohormone. İt is thought that vitamin D deficiency is responsible for Lots of diseases which includes MS . In this study, we aimed to show the relationship between serum vitamin D level and MS.Objective: In our research we wanted to show the serum vitamin D levels in MS patients.Methods: We included 106 patients (76 female, 30 male) to our study. Participants were divided into two groups as patient and control group. Serum vitamin D levels were evaluated.We excluded patients with known liver or renal disease. Liver enzymes and blood creatinine of the patients included in the study were normal.Results: There was a statistically significant difference when comparing two groups of serum vitamin D results. Serum vitamin D levels were lower in the control group. No correlation was found between vitamin D and age. There was no correlation between vitamin D and gender. According to the vitamin D level reference interval in the MS group, 28 patients had deficiency, 17 patients had failure, and 12 patients were normal. In the control group, according to the vitamin D level reference range, 35 patients had deficiency, 11 patients had failure and 3 patients were normal.Conclusion: In this study conducted with limited facilities, lower vitamin D levels in the control group suggested that vitamin D levels may be low when the population is examined in general. Vitamin D support throughout the population may reduce the prevalence of other diseases thought to be caused by vitamin D deficiency as well as MS.